RESPON PERTUMBUHAN STEK PUCUK DAN STEK BATANG GANITRI (Elaeocarpus ganitrus Roxb.) TERHADAP HORMON PERTUMBUHAN - Filopor, .; Ismanto, .; Prameswari, Diana (Universitas Pakuan, 2023)
Ganitri (Elaeocarpus ganitrus Roxb) is a fast-growing tree species that is widely found in Indonesia, Malaysia, Myanmar, and Thailand. Ganitri seedlings’ generative propagation takes a long time because the seed coat is very hard, causing difficulty to germinate, therefore it is conducted vegetatively using stem and shoot cuttings with hormone treatment. The research objective was to obtain growth response of shoot cuttings and ganitri stem cuttings to hormone administration. The research was conducted in Silviculture greenhouse at Center for Standardization of Instruments for Sustainable Forest Management in Bogor. It used a Completely Randomized Design with a factorial pattern consisting of 2 factors. The first factor is cutting material: shoot cuttings and stem cuttings. The second factor is phytohormones: Rootone-F and coconut water. The results showed shoot cuttings with Rootone-F treatment gave the best growth compared to other treatment combinations. This was indicated by percent growing cuttings, percent rooted cuttings, root length, shoot wet weight, root wet weight, shoot dry weight and root dry weight which were higher with values of 63.33%, 53.0%, 8.10 cm, 2.92 grams, 0.28 grams, 1.33 grams, and 0.21 grams respectively. Thus, shoot cuttings survival with Rotoone-F hormone had a higher result than stem cuttings, reaching 63.33%.